Digital Marketing Strategies and Increasing the Economic Value of the Sports Industry: A Global Literature Analysis - Utomo, Andy Widhiya Bayu; Pujiati, Amin; Asyhari, Adit Tarauna Cholis; Saputra, Sylvana Yaka; Runesi, Salmon; Puriana, Ramadhany Hananto; Kuryanto, Mohammad Syaffrudin; Jumesam, Jumesam (Universitas Hamzanwadi, 2025)
With technological advancements, the sports sector increasingly relies on digital marketing, including social media usage, data-driven marketing, and other digital technologies, to expand reach and boost revenue. This study aims to analyze how digital marketing strategies contribute to enhancing the economic value of the sports industry. This research uses a systematic literature review approach to analyze various relevant studies, focusing on the contributions of digital marketing to revenue, fan engagement, and brand loyalty in the global sports industry. The results show that digital marketing strategies, such as social media engagement, content marketing, augmented reality (AR) use, and hybrid business models, are highly effective in increasing the economic value of the sports industry. Additionally, the development of digital infrastructure and the use of advanced technologies also contribute to market expansion and enhanced fan engagement. This study also identifies challenges related to digital piracy and the lack of cohesive strategies in some sports organizations. Therefore, the effective implementation of digital marketing strategies can strengthen the sports industry's position in the global market.